2017
DOI: 10.1186/s12951-017-0298-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of PLGA-modified nanoparticles in 3D cell culture models of hypo-vascularized tumor tissue

Abstract: BackgroundAdvanced stage cancer treatments are often invasive and painful—typically comprised of surgery, chemotherapy, and/or radiation treatment. Low transport efficiency during systemic chemotherapy may require high chemotherapeutic doses to effectively target cancerous tissue, resulting in systemic toxicity. Nanotherapeutic platforms have been proposed as an alternative to more safely and effectively deliver therapeutic agents directly to tumor sites. However, cellular internalization and tumor penetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 57 publications
5
67
0
Order By: Relevance
“…With the intent to reduce the amount of data acquired, we next determined an appropriate image acquisition regime in the xyz dimensions ( Figure A; Supporting Information). We used this as a strategy to identify the widest cross‐section or equatorial (EQ) plane of individual 3D structures (Figure B), which can then be used for assessment of nanoparticle penetration to the center of the spheroid . An initial series of 70 z ‐planes with 0.5 µm spacing was acquired in a 10.4 mm 2 of the well area (≈ 30% of the total surface).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With the intent to reduce the amount of data acquired, we next determined an appropriate image acquisition regime in the xyz dimensions ( Figure A; Supporting Information). We used this as a strategy to identify the widest cross‐section or equatorial (EQ) plane of individual 3D structures (Figure B), which can then be used for assessment of nanoparticle penetration to the center of the spheroid . An initial series of 70 z ‐planes with 0.5 µm spacing was acquired in a 10.4 mm 2 of the well area (≈ 30% of the total surface).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this feature, we implemented a protocol to streamline in situ fluorescence processing and imaging, thereby avoiding manually‐intensive procedures (e.g., steps such as transfer of spheroids, embedding, cryosectioning, etc.) typically adopted in many 3D drug‐screening assays and studies assessing NP‐mediated drug penetration using fluorescence microscopy . The 3D cell culture approach described in this study enables the positioning of spheroids, once fixed, on a common optical plane .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11] In contrast, small (<500 nm) or neutrally charged ''stealth'' carriers more rapidly and effectively penetrate the tightly spaced and negatively charged vitreous or mucosal environments. [12][13][14] In previous work, we have assessed the binding and internalization mechanisms of unmodified, MPG, and poly(ethylene glycol) (PEG)-modified NPs in cells [15][16][17] and found that surface-modification with MPG results in higher cell association and binding, likely due to the positive zeta-potential, relative to more negatively charged unmodified and neutrally charged PEG NPs. Regardless of surface-modification (unmodified, MPG-modified, or PEG-modified), cell internalization occurred via clathrin-mediated endocytosis.…”
mentioning
confidence: 99%